Characterizing commercial cattle farms in Namibia: Risk, management and sustainability - Roland Olbrich; Martin F. Quaas; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
Commercial cattle farming in Namibia, a prime example of livestock farming in semi-arid rangelands, is subject to a variety of risks, predominant among which is precipitation risk. At the same time it suffers from rangeland degradation that is at least partly due to inadequate management. We characterize cattle farms through descriptive statistics and cluster analysis using data that we elicited in August 2008 through mail-in questionnaires and in-field experiments. We find that cattle farms are highly heterogeneous in the majority of individual characteristics. Heterogeneity is also observed when analyzing characteristics jointly through the cluster analysis which suggests classification of farms into three distinct clusters. This classification is predominantly driven by environmental condition and financial risk management, and to a lesser extent by organizational structure of farms or ethnicity. Overall, our study is the first to provide a comprehensive characterization of this system in respect to risk, management and sustainability.
Keywords: Q12; Q15; Q57; 330; cattle farming; semi-arid rangelands; Namibia; empirical survey; perceived risk; management; risk and time preferences; normative views; sustainability; Rinderhaltung; Trockenklima; Risikomanagement; Nachhaltige Entwicklung; Namibia